Environmental Assessment of Lithium-Ion Battery Lifecycle and of Their Use in Commercial Vehicles - Livia Nastasi; Silvia Fiore (Batteries, 2024)
This review analyzed the literature data about the global warming potential (GWP) of the lithium-ion battery (LIB) lifecycle, e.g., raw material mining, production, use, and end of life. The literature data were associated with three macro-areas—Asia, Europe, and the USA—considering common LIBs (nickel manganese cobalt (NMC) and lithium iron phosphate (LFP)). The GWP (kgCO2eq/kg) values were higher for use compared to raw material mining, production, and end of life management for hydrometallurgy or pyrometallurgy. Considering the significant values associated with the use phase and the frequent application of secondary data, this study also calculated the GWP of LIBs applied in public urban buses in Turin, Italy. The 2021 fleet (53% diesel, 36% natural gas, and 11% electric buses) was compared to scenarios with increasing shares of hybrid/electric. The largest reduction in CO2eq emissions (−41%) corresponded to a fleet with 64% electric buses. In conclusion, this review highlighted the bottlenecks of the existing literature on the GWP of the LIB lifecycle, a lack of data for specific macro-areas for production and use, and the key role of public transportation in decarbonizing urban areas.